Early feasibility testing of a web-based mind-body resiliency program for adults with neurofibromatosis: The NF-Web study - Ethan G. Lester; Nathan S. Fishbein; Annabel Peterson; Ana-Maria Vranceanu (PEC Innovation, 2022)
Objectives: We aimed to test early feasibility, acceptability, and signals of improvement after the 8-week individually delivered asynchronous, web-based mind-body program (NF-Web) modeled after the synchronous group-based live video program (Relaxation Response Resiliency Program for NF; 3RP-NF). Methods: Two cohorts (cohort 1 n = 14, cohort 2 n = 14) completed baseline and posttest (feasibility markers, t-tests). Results: Enrolled participants (N = 28; 80% of those eligible) completed baseline (N = 28; 100% of sample) and posttests (N = 25; 89.3%). Video lesson (58.0%) and homework (70.9%) completion were fair to good. Satisfaction (M = 8.85/10; SD = 2.35), credibility (M = 7.07/10; SD = 1.44), and expectancy (M = 6.68/10; SD = 2.10) were good to excellent. Participation was associated with statistically significant pre-to-post positive changes in quality of life (QoL; Physical, Psychological, Social, and Environmental,; p < 0.05) and emotional distress (depression, anxiety, and stress; p < 0.05). Pain intensity and interference did not improve significantly (p > 0.05) after participation. Conclusions: NF-Web demonstrates initial feasibility, acceptability, and signals of improvement. Results support future trials to ascertain efficacy. Innovation: Web-based programs may be valuable for individuals with rare illness who prefer to learn skills on their own timeline, have barriers to live video participation, and who also have apprehensions about interacting with others during treatment.